Gambaran Status Gizi pada Anak Balita di Desa Keude Nibong dan Sumbok Rayeuk Kabupaten Aceh Utara - Lisanan Zakira; Hafni Zahara; Noeroel Arham (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Nutritional status is a health condition that indicates whether or not nutrients are sufficient in the body. This is influenced by eating habits and the body's ability to absorb nutrients. Nutritional status assessment can be done by body measurements, diet analysis, or laboratory tests. This indicator shows the extent to which nutritional needs are met to support body function and growth. This study aims to determine the nutritional status of toddlers in Keude Nibong Village and the factors that influence it. The research design used a quantitative approach with a correlation method, involving 35 toddlers as samples. The results showed that most toddlers were male (52%) and most were aged 24-35 months and 48-59 months (23.7% each). A total of 29 toddlers (83%) had good nutritional status, while 6 toddlers (17%) were malnourished. The nutritional condition of toddlers was generally good, but regular monitoring by health workers and the village government through integrated health posts (posyandu) is needed. Further research is recommended to examine factors such as diet, economy, and parental education that influence children's nutritional status.